KEPERCAYAAN BUBUHAN KUMAI terhadap Tuhan dan Makhluk Halus - Al-Kumayi, Sulaiman (Sabda: Jurnal Kajian Kebudayaan, 2012)
One important part of the belief system is a belief which covers trust in God the Almighty and trust regarding the presence of supernatural being. In relation to Bubuhan Kumai, this community has built a system of belief which reflects their understanding and interpretation of Islam religious devotion which they embrace. Islam religion is not immediately able to remove local beliefs deeply rooted in the memory of Bubuhan Kumai communities. This article describes about the belief system of Bubuhan Kumai which covers the belief to the God the Almighty and belief of the presence of the supernatural being, employing experiences of the participants of the culture studied.